KINERJA PEMASARAN PT. PERKEBUNAN NUSANTARA III (PERSERO) (JASEP, 2015)
Marketing Performance PT. Perkebunan Nusantara III (Persero) consist the analysis of (1) the ability of marketing with Structural Equation Modeling (SEM) and Confirmatory Factor Analysis (CFAs), (2) Audit marketing strategy based Strategic Marketing Plus 2000, and (3) Marketing achievement in statistic different test methods. The analysis result of marketing capabilities, remaining 12 indicators and 4 marketing capabilities of CPO commodity those are Product Development, Selling, Marketing Planning, and Marketing Implementation. For the Rubber commodity remaining 9 indicators and 3 marketing capabilities, namely Selling, Marketing Planning, and Marketing Implementation. On CPO commodity capability of Selling and Marketing Implementation has a highest positive correlations value. Capability of Product Development and Marketing Implementation has a lowest positive correlations value. For Rubber commodity a highest positive correlations are capability of Selling and Marketing Implementation. Marketing Planning and Marketing Implementation has a lowest positive correlations value. With the method of Strategic Marketing Plus 2000 is known that the marketing strategies of PT. Perkebunan Nusantara III is relatively lagging behind, which means it does not have a competitiveness. The analysis conducted on the marketing achievement CPO and Rubber based on quantum and value of sales can be achieved according to plan except sales quantum of Rubber.